Genome Sequence of Rhizobium lupini HPC(L) Isolated from Saline Desert Soil, Kutch (Gujarat) - Agarwal, Leena (American Society for Microbiology, 2013)
The Rhizobium lupini strain HPC(L) was isolated from saline desert soil. It grows on minimal media supplemented with CaCO(3) as a carbon source. It can also grow under both oligotrophic and heteroptrophic conditions. We report the annotated genome sequence of this strain in a 5.27-Mb scaffold.